Adsorption of Cu(II) on humic acids derived from different organic materials - Cui-lan LI; Fan JI; Shuai WANG; Jin-jing ZHANG; Qiang GAO; Jing-gui WU; Lan-po ZHAO; Li-chun WANG; Li-rong ZHENG (Journal of Integrative Agriculture, 2015)
The adsorption of Cu(II) from aqueous solution onto humic acid (HA) which was isolated from cattle manure (CHA), peat (PHA), and leaf litter (LHA) as a function of contact time, pH, ion strength, and initial concentration was studied using the batch method. X-ray absorption spectroscopy (XAS) was used to examine the coordination environment of the Cu(II) adsorbed by HA at a molecular level. Moreover, the chemical compositions of the isolated HA were characterized by elemental analysis and solid-state 13C nuclear magnetic resonance spectroscopy (NMR). The kinetic data showed that the adsorption equilibrium can be achieved within 8 h. The adsorption kinetics followed the pseudo-second-order equation. The adsorption isotherms could be well fitted by the Langmuir model, and the maximum adsorption capacities of Cu(II) on CHA, PHA, and LHA were 229.4, 210.4, and 197.7 mg g−1, respectively. The adsorption of Cu(II) on HA increased with the increase in pH from 2 to 7, and maintained a high level at pH>7. The adsorption of Cu(II) was also strongly influenced by the low ionic strength of 0.01 to 0.2 mol L−1 NaNO3, but was weakly influenced by high ionic strength of 0.4 to 1 mol L−1 NaNO3. The Cu(II) adsorption on HA may be mainly attributed to ion exchange and surface complexation. XAS results revealed that the binding site and oxidation state of Cu adsorbed on HA surface did not change at the initial Cu(II) concentrations of 15 to 40 mg L−1. For all the Cu(II) adsorption samples, each Cu atom was surrounded by 4 O/N atoms at a bond distance of 1.95 Å in the first coordination shell. The presence of the higher Cu coordination shells proved that Cu(II) was adsorbed via an inner-sphere covalent bond onto the HA surface. Among the three HA samples, the adsorption capacity and affinity of CHA for Cu(II) was the greatest, followed by that of PHA and LHA. All the three HA samples exhibited similar types of elemental and functional groups, but different contents of elemental and functional groups. CHA contained larger proportions of methoxyl C, phenolic C and carbonyl C, and smaller proportions of alkyl C and carbohydrate C than PHA and LHA. The structural differences of the three HA samples are responsible for their distinct adsorption capacity and affinity toward Cu(II). These results are important to achieve better understanding of the behavior of Cu(II) in soil and water bodies in the presence of organic materials.